РОЛЬ МУЗЫКАЛЬНО-ТЕОРЕТИЧЕСКИХ ДИСЦИПЛИН В ПРОЦЕССЕ ПРОФЕССИОНАЛЬНОГО СТАНОВЛЕНИЯ УЧИТЕЛЯ МУЗЫКИ - Надырова, А.Б. (SCIENCE and SOCIETY, 2018)
The article is devoted to the issues of professional training of teachers in Music. Theoretical preparation let the teacher in Music understand the concepts of musical art, main regularities of history and theory of music in their inter relation.
Keywords: musical lesson; pedagogical process; enlighentment; method; musical art; musical intellection